Pertunjukan Kompang Bengkalis: dari Arak-Arakan ke Seni Pertunjukan - Yosi Ramadona; Nursyirwan Nursyirwan (LPPMPP Institut Seni Indonesia Padangpanjang, 2014)
This writing is the result of research with the purpose to describe thedevelopment of kompang music in Meskom community in Bengkalis, fromthe music of parade to Attractive Performance. The tradition of kompangparade in Bengkalis community was formerly part of Islamic religiuosteaching, an integral part of Islam-related ceremonies or parties. But nowkompang music has developed from music of parade to music ofentertainment known as Kompang Attraction Performance. In order to seethe development of kompang from the music of parade to music ofperformance, this research used a qualitative method with descriptive analysis using theories of function and performance. The development ofkompang from music of parade to Kompang Performance Attraction wasbased on the needs of community for a more attractive art performanceand entertainment. The development was done by adding some attractivemovements into the performance combined with kompang game attractionwithout reducing the essence of the performance itself, the Islamic teaching